2021
DOI: 10.3389/fchem.2021.682862
|View full text |Cite
|
Sign up to set email alerts
|

Using Network Pharmacology and Molecular Docking to Explore the Mechanism of Shan Ci Gu (Cremastra appendiculata) Against Non-Small Cell Lung Cancer

Abstract: Background: In recent years, the incidence and mortality rates of non-small cell lung cancer (NSCLC) have increased significantly. Shan Ci Gu is commonly used as an anticancer drug in traditional Chinese medicine; however, its specific mechanism against NSCLC has not yet been elucidated. Here, the mechanism was clarified through network pharmacology and molecular docking.Methods: The Traditional Chinese Medicine Systems Pharmacology database was searched for the active ingredients of Shan Ci Gu, and the releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…To evaluate the binding ability of NaB to the 5 core target genes, we performed molecular docking and plotted images. Lower score of binding energy indicates stronger binding affinity of the docked complex; while binding energy < 0 kcal/mol indicates that ligand molecules can spontaneously bind to the receptor proteins ( 25 , 27 , 36 ). Our results revealed that the binding energies of NaB binding to the 5 core target genes were all less than 0 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the binding ability of NaB to the 5 core target genes, we performed molecular docking and plotted images. Lower score of binding energy indicates stronger binding affinity of the docked complex; while binding energy < 0 kcal/mol indicates that ligand molecules can spontaneously bind to the receptor proteins ( 25 , 27 , 36 ). Our results revealed that the binding energies of NaB binding to the 5 core target genes were all less than 0 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Then, enter the potential targets for melanoma treatment into the STRING database, and set the target as “Homo” to construct a protein–protein interaction (PPI) diagram of potential targets for melanoma treatment ( Supplementary Figure S2 ). Potential target pathway enrichment was generated through the DAVID 6.8 database ( Wang et al, 2021 ). Finally, Cytoscape v3.8.2 software ( https://cytoscape.org/download.html ) was used to construct a “C-T-P" network of 44 compounds, 18 targets, and 10 signaling pathways closely related to melanoma to elucidate the effective mechanism of LCF anti-melanoma.…”
Section: Methodsmentioning
confidence: 99%
“…Active pockets were built and saved as protein data bank (PDB), partial charge (Q), and atom type (T) (PDBQT) files. Then, each active site was docked with the compound ( Wang Y. et al, 2021 ). According to the results of molecular docking, the conformation with the most stable structure and lowest energy was selected and imported into PyMoL 1.8 ( https://pymol.org ) together with the protein ( Shen et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%